Genetic loci on chromosome 5 are associated with circulating levels of interleukin-5 and eosinophil count in a European population with high risk for cardiovascular disease. (May 2016) - McLeod, Olga; Silveira, Angela; Valdes-Marquez, Elsa; Björkbacka, Harry; Almgren, Peter; Gertow, Karl; Gådin, Jesper R.; Bäcklund, Alexandra; Sennblad, Bengt; Baldassarre, Damiano; Veglia, Fabrizio; Humphries, Steve E.; et al.
Highlights: Two loci identified for IL-5 levels on chromosomes and 14. One locus on chromosome 5 was identified for eosinophil count. The chromosome 5 loci are in close proximity, but independent and non-overlapping. IL-5-associated SNPs were not associated with carotid intima-media thickness. Eosinophil-associated SNPs were not associated with carotid intima-media thickness. Abstract: IL-5 is a Th2 cytokine which activates eosinophils and is suggested to have an atheroprotective role. Genetic variants in the IL5 locus have been associated with increased risk of CAD and ischemic stroke. In this study we aimed to identify genetic variants associated with IL-5 concentrations and apply a Mendelian randomisation approach to assess IL-5 levels for causal effect on intima-media thickness in a European population at high risk of coronary artery disease. We analysed SNPs within robustly associated candidate loci for immune, inflammatory, metabolic and cardiovascular traits. We identified 2 genetic loci for IL-5 levels (chromosome 5, rs56183820, BETA = 0.11, P  = 6.73E −5 and chromosome 14, rs4902762, BETA = 0.12, P  = 5.76E −6 ) and one for eosinophil count (rs72797327, BETA = −0.10, P  = 1.41E −6 ). Both chromosome 5 loci were in the vicinity of the IL5 gene, however the association with IL-5 levels failed to replicate in a meta-analysis of 2 independent cohorts (rs56183820, BETA = 0.04, P  = 0.2763, I 2  = 24, I 2  −  P  = 0.2516). No significant associations were observed between SNPs associated with IL-5 levels or eosinophil count and IMT measures. Expression quantitative trait analyses indicate effects of the IL-5 and eosinophil-associated SNPs on RAD50 mRNA expression levels (rs12652920 (r2 = 0.93 with rs56183820) BETA = −0.10, P  = 8.64E −6 and rs11739623 (r2 = 0.96 with rs72797327) BETA = −0.23, P  = 1.74E −29, respectively). Our data do not support a role for IL-5 levels and eosinophil count in intima-media thickness, however SNPs associated with IL-5 and eosinophils might influence stability of the atherosclerotic plaque via modulation of RAD50 levels.